Implementasi Senam Kaki Untuk Menurunkan Kadar Gula Darah pada Penderita Diabetes Melitus Tipe 2 di Rumah Sakit Tentaratk Iv 01.07.01 Pematangsiantar - Aradea, Rizky; Sari Purba, Wulan (Journal of Comprehensive Science, 2024)
Diabetes is a chronic metabolic disease characterized by increased blood glucose levels, which over time causes serious damage to the heart, blood vessels, eyes, kidneys and nerves. The aim of this study is to describe nursing care in the application of foot exercises to reduce blood sugar levels in patients with type 2 diabetes mellitus. Diabetes is a chronic metabolic disease characterized by elevated blood glucose levels, which over time causes serious damage to the heart, blood vessels, eyes, kidneys and nerves. The aim of this study is to describe nursing care in the application of foot exercises to reduce blood sugar levels in patients with type 2 diabetes mellitus. leg exercises can reduce blood sugar levels. The application of foot exercises can reduce blood sugar levels in type 2 diabetes mellitus patients.